The Evolution, progression and Impact of ISO 9000 in the manufacturing organizations around the world and India: An Analysis - PRIYANSHU, DEEPA; KHAN, RUBINA LIYAKAT; MAQDADI, MAHERA; VASHISHTA, MONISHA GUPTA (The journal of contemporary issues in business and government, 2021)
In order to survive in the combative market, the companies have to develop a kind of mechanism in order to be in the preferred positions from their competitors. They should identify mechanism to make sure about their superiority from their competitors. Superiority from others can be achieved through many factors. Quality Certification and Assurance has become an unprecedented way to differentiate from the lots. Quality Certification has also emerged as a demand of Customers. The meaning of Quality has perplexity but no one can deny its importance in creation of differentiation status for the companies. Quality has been undisputed factor of preference for customer satisfaction. This paper is a deliberate attempt to understand the evolution, reasons and benefits derived by implementing ISO 9000 in their organization.